Lightweight high-strength bio-based chitosan hybrid aerogel and preparation method thereof
By preparing lightweight, high-strength bio-based chitosan hybrid aerogel, the problems of brittleness and powder loss in existing aerogel materials in the construction field are solved, and the performance matching of low density, high strength and low thermal conductivity is achieved, which is suitable for the application of building materials.
Patent Information
- Application Number
- CN202411675721.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
AI Technical Summary
The existing aerogel materials have problems such as brittle and brittle quality, powder loss, slag loss, raw materials toxic, complex preparation process and high cost, and are difficult to directly apply in construction and other fields.
Lightweight high-strength bio-based chitosan hybrid aerogel is used, and the preparation method includes mixing chitosan, polyvinyl alcohol, nanocellulose and metal oxides or non-metal oxides in a specific proportion, adding crosslinking agent for crosslinking and polymerization, heating and aging and solvent replacement through procedure, and finally preparing by CO2 supercritical fluid drying.
制备出的气凝胶材料具有低密度、高强度和低热导率的特点,密度低至0.058g/cm3,常温常压热导率为0.018~0.028W/(m·K),压缩应变为3%时,压缩应力达到0.210~0.276MPa,适合建筑建材的应用。
Smart Images

Figure CN119505381A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a thermal insulation material and a preparation method thereof, and in particular to a light and high-strength bio-based chitosan hybrid aerogel and a preparation method thereof. Background Art
[0002] Building energy consumption ranks first in my country's total social energy consumption. Building thermal insulation materials, especially high-efficiency thermal insulation materials, are one of the important ways to alleviate building energy consumption and promote sustainable economic development. Aerogel materials, as a new type of high-efficiency thermal insulation material, have been put into practical use in the fields of aerospace and some civil thermal insulation. However, the most widely used SiO2 aerogel material itself has defects such as brittleness, powder loss, slag loss, toxic raw materials, complex preparation process and high cost, which makes the existing SiO2 aerogel material cannot be directly used in the fields of construction. Therefore, it is of great significance to develop environmentally friendly, lightweight, high-strength, high-performance and widely used thermal insulation materials.
[0003] Chitosan aerogel material is a new type of bio-based aerogel thermal insulation material. It has abundant raw material sources. The main raw material, chitosan, is a derivative of chitin, the second largest natural polymer material in nature. It provides structure and stability for the exoskeleton of crustaceans, insects and fungal cell walls, which can make up for the problem of insufficient strength and brittleness of aerogel. It is environmentally friendly and renewable. At the same time, combined with the advantages of light weight and low thermal conductivity of aerogel, chitosan aerogel occupies an unparalleled position in the field of low-carbon environmental protection and thermal insulation. At present, most of the publicly available chitosan aerogels are used in the fields of biomedicine, adsorption and catalysis, and their application in the field of thermal insulation materials is still lacking. For example, Chinese patent CN115536896A provides a chitin-chitosan double cross-linked aerogel and its preparation method. The invention supplements the template technology and chemical cross-linking method, uses template, cross-linking and freeze-drying technology to obtain HPS-aerogel, realizes macropore-mesopore-micropore 3D multi-level network structure, and improves the mechanical properties at the same time. However, the mechanical properties of the invention are still poor. When the strain is 50%, the stress is only 0.415MPa, and when the strain is 80%, the stress reaches 1.472MPa, and the density is relatively high, reaching 1.43g / cm 3 , thermal conductivity data have not been reported. Zhang et al. (Carbohydrate Polymers, 2023, 320, 121245) reported a chitosan / silica hybrid aerogel material with excellent hydrophobicity and mechanical strength, involving a silica phase hybridization strategy to enhance the synergistic performance of the CHAs series, with a density as low as 0.149 g / cm 3, the thermal conductivity at room temperature and pressure is 0.024~0.034W / (m·K), which not only improves its hydrophobicity, but also enhances its mechanical strength. Under the condition of 3% compression strain, the compression stress is 0.188MPa, but from the perspective of practical application, the mechanical properties of this material still need to be further improved. Therefore, if the bio-based chitosan aerogel material can meet the requirements of light weight and low thermal conductivity at room temperature and pressure, and has high strength performance, it will have irreplaceable advantages and broad application prospects. However, how to match the light weight, low thermal conductivity at room temperature and pressure and high strength performance of bio-based chitosan aerogel is a technical problem that has not yet been addressed in the field of thermal insulation. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a lightweight and high-strength bio-based chitosan hybrid aerogel and a preparation method thereof in view of the problems of existing aerogel materials such as brittleness, powdering and slag dropping, toxic raw materials, complex preparation process and high cost, so that the aerogel material has the advantages of light weight, low density, high strength, excellent thermal insulation and green environmental protection.
[0005] The light and high-strength bio-based chitosan hybrid aerogel of the present invention is prepared from chitosan (solution concentration of 0.4-2.3wt.%), polyvinyl alcohol (solution concentration of 1-8wt.%), nanocellulose (solid content of 0.5-5.5wt.%) and metal oxide or non-metal oxide as raw materials, mixed in a mass ratio of 1:0.3-0.8:0.03-0.2:0.01-0.1 (the amounts of the remaining added phases are all based on the chitosan solution of the ternary solvent of acetic acid, ethanol and water), and stirred evenly to obtain a mixed solution; a crosslinking agent (solution concentration of 4-12wt.%) is added to the mixed solution, and the mass ratio of the crosslinking agent to the mixed solution is 0.15-0.35:1, and a bio-based chitosan gel is prepared by a sol-gel method; and the prepared aerogel is subjected to programmed staged temperature aging, solvent replacement, and finally dried by CO2 supercritical fluid. The bio-based chitosan hybrid aerogel prepared by the present invention has a nanoporous three-dimensional network skeleton and has the characteristics of low density, high strength and low thermal conductivity. The density is as low as 0.058g / cm 3 The thermal conductivity at room temperature and pressure is 0.018~0.028W / (m·K). When the compressive strain is 3%, the compressive stress reaches 0.210~0.276MPa.
[0006] The method for preparing the lightweight and high-strength bio-based chitosan hybrid aerogel of the present invention comprises the following steps:
[0007] The first step is to prepare a bio-based chitosan solution by:
[0008] The bio-based chitosan powder is dissolved in a mixed solvent of acetic acid, ethanol and water, and stirred to dissolve evenly to obtain a bio-based chitosan solution. It is worth noting that the amounts of the additives described below are all based on the bio-based chitosan solution of the ternary solvent of acetic acid, ethanol and water.
[0009] The bio-based chitosan powder has a deacetylation degree of 35% to 95%, a viscosity of 99 to 510 mPa·s, and a bio-based chitosan solution concentration of 0.4 to 2.3 wt.%. Preferably, the bio-based chitosan powder has a deacetylation degree of 68% to 95%, a viscosity of 99 to 205 mPa·s, and a bio-based chitosan solution concentration of 0.6 to 1.7 wt.% (referring to the concentration of the bio-based chitosan powder in the mixed solvent).
[0010] The purity of acetic acid in the mixed solvent is 99.5% to 99.9%, the purity of ethanol is 99.3% to 99.9%, and the mass ratio of acetic acid, ethanol and water in the mixed solvent is 1:60 to 90:40 to 60.
[0011] The second step is to prepare the bio-based chitosan hybrid sol as follows:
[0012] 2.1 Add polyvinyl alcohol solution to the bio-based chitosan solution prepared in the first step, stir evenly, then add metal oxide or non-metal oxide, after the metal oxide or non-metal oxide is evenly dispersed, add nanocellulose and continue stirring to form van der Waals forces, hydrogen bonds and physical entanglements between chitosan molecular chains, polyvinyl alcohol molecular chains and nanocellulose molecules to obtain a homogeneous mixed solution; the polyvinyl alcohol solution has a degree of alcoholysis of 68% to 99%, a viscosity of 18 to 113 mPa·s, and a concentration of 1 to 8 wt.%, preferably a degree of alcoholysis of 86 to 90 mol%, a viscosity of 78 to 113 mPa·s, and a concentration of 2 to 6 wt.%.
[0013] The metal oxide or non-metal oxide is any one of iron oxide, aluminum oxide, zirconium oxide, silicon oxide, and calcium oxide, or a mixture of two or more of them, and the amount added is 1% to 10% of the mass of the chitosan solution, with the chitosan solution as the reference. Zirconium oxide (ZrO2) and silicon oxide (SiO2) are two typical oxides that are preferred.
[0014] The nanocellulose is any one of waste paper nanocellulose, graphene nanocellulose, bacterial nanocellulose, fungal nanocellulose, and wood nanocellulose, or a mixture of two or more of them, with a solid content of 0.5 to 5.5 wt.%, and an aspect ratio of 15 to 55, preferably a solid content of 0.8 to 4 wt.%, and an aspect ratio of 26 to 42.
[0015] 2.2 Add the crosslinker solution to the homogeneous mixed solution and stir evenly to make the mixed solution with the crosslinker solution undergo crosslinking polymerization. The aldehyde group in the crosslinker and the amino group in the chitosan molecule undergo acetal reaction to obtain a homogeneous bio-based chitosan hybrid sol; the mass ratio of the homogeneous mixed solution to the crosslinker solution is 1:0.15-0.35.
[0016] The crosslinking agent in the crosslinking agent solution is any one of formaldehyde, acetaldehyde, propionaldehyde, glutaraldehyde, o-phthalaldehyde, isophthalaldehyde, terephthalaldehyde, or a mixed solvent of two or more thereof, with a concentration of 4 to 12 wt.%, preferably formaldehyde, with a concentration of 7 to 12 wt.%.
[0017] The third step is to prepare the bio-based chitosan hybrid final gel as follows:
[0018] 3.1 The homogeneous bio-based chitosan hybrid sol prepared in the second step is aged at room temperature to form a bio-based chitosan hybrid initial gel;
[0019] 3.2 Place the bio-based chitosan hybrid initial gel in a water bath and continue aging with programmed temperature increase, while replacing the solvent with an organic alcohol solvent. The programmed temperature increase steps are from room temperature (25°C) to 35°C, 45°C, 55°C, and 65°C in sequence, with a heating rate of 4 to 6°C / h. Replace with an organic solvent once in each stage and keep warm for 2 to 6 hours;
[0020] 3.3 Continue to raise the temperature to 75°C at the same heating rate as step 3.2, and keep warm for 2 to 6 hours. Place the bio-based chitosan hybrid gel at this time in analytical pure ethanol solvent at room temperature to observe whether the bio-based chitosan hybrid initial gel can float directly. If it can float directly, it indicates that the gel aging and solvent replacement are completed, and the bio-based chitosan hybrid final gel is obtained.
[0021] The organic solvent used in the solvent replacement is any one of methanol, ethanol, isopropanol, and n-propanol (the purity of methanol, ethanol, isopropanol, and n-propanol is required to be above 99%), or a mixed solvent of two or more thereof, preferably ethanol. The purity of the analytical pure ethanol solvent is 99.3% to 99.9%.
[0022] The fourth step is to prepare a lightweight and high-strength bio-based chitosan hybrid aerogel by:
[0023] The final bio-based chitosan hybrid gel obtained in the third step is placed in a drying kettle for CO2 supercritical fluid drying. After drying, the pressure is released to obtain a lightweight and high-strength bio-based chitosan hybrid aerogel.
[0024] The CO2 supercritical fluid drying pressure is 8-19 MPa, the drying time is 6-20 h, and the temperature is 37-82° C. Preferably, the supercritical fluid drying pressure is 13-18 MPa, the drying time is 7-16 h, the temperature is 48-63° C., and the pressure release rate is 90-243 kPa / min, preferably 118-178 kPa / min.
[0025] The following technical effects can be obtained by using the present invention:
[0026] 1. The method for preparing light and high-strength bio-based chitosan hybrid aerogel of the present invention, in the second step, the aldehyde group in the cross-linking agent and the amino group in the chitosan molecule undergo acetal reaction, and the high molecular weight polymer polyvinyl alcohol, metal oxide or non-metal oxide in the second step all have high activity, so that the molecules interact with each other, and the skeleton network structure of the bio-based chitosan gel is enhanced; in addition, the nanocellulose in the second step is dispersed in the above-mentioned mixed solution system, forming hydrogen bonds or reacting with other groups to form a three-dimensional network structure of nanoparticles, so that the bio-based chitosan hybrid aerogel presents good enhanced and toughened high-strength performance. Then, the third step is programmed heating, heat preservation, and aging to further improve the skeleton strength and cross-linking density of the bio-based chitosan hybrid aerogel; the fourth step is CO2 supercritical fluid drying method to maintain the porous network structure of the bio-based chitosan hybrid aerogel, the rich network skeleton structure of the bio-based chitosan hybrid aerogel is maintained, and the drying shrinkage of the aerogel is controlled.
[0027] 2. The density of the lightweight and high-strength bio-based chitosan hybrid aerogel prepared by the method of the present invention is 0.058-0.206 g / cm 3 The thermal conductivity at room temperature and pressure is 0.018~0.028W / (m·K). When the compressive strain is 3%, the compressive stress reaches 0.210~0.276MPa, which solves the technical problem of lightweight and high-strength performance synergistic optimization of bio-based chitosan aerogel and has low thermal conductivity at room temperature and pressure, and can meet the standard requirements for basic application of building materials.
[0028] 3. The method for preparing the lightweight and high-strength bio-based chitosan hybrid aerogel provided by the present invention uses readily available raw materials, is environmentally friendly, has low equipment requirements, has a simple preparation technology route, and is highly operational. It is suitable for industrial production and market entry, and is convenient for large-scale application in the field of construction and building materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is an overall flow chart of the method for preparing the lightweight and high-strength bio-based chitosan hybrid aerogel of the present invention. DETAILED DESCRIPTION
[0030] The present invention is further described below with reference to examples, but these examples shall not be used to limit the scope of protection of the present invention.
[0031] Example 1
[0032] The first step is to prepare the bio-based chitosan solution:
[0033] 0.4 g of bio-based chitosan powder (deacetylation degree of 75%, viscosity of 205 mPa·s) was dissolved in 99.6 g of a mixed solvent of acetic acid (purity 99.5%), ethanol (purity 99.5%) and water (mass ratio of 1:80:44), and stirred evenly to obtain 100 g of a bio-based chitosan solution with a concentration of 0.4 wt.%.
[0034] The second step is to prepare the bio-based chitosan hybrid sol:
[0035] 2.1 Add 50 g of 1 wt.% polyvinyl alcohol solution (with a degree of alcoholysis of 86% and a viscosity of 105 mPa·s) to the 100 g bio-based chitosan solution prepared in the first step, and continue stirring until uniform. Then, slowly add 6 g of zirconium oxide to the mixed solution and stir for 1 h. After uniform dispersion, add 18 g of 0.8 wt.% nanocellulose (with an aspect ratio of 35) and stir to obtain a homogeneous mixed solution.
[0036] 2.2 Add 26 g of 4 wt.% formaldehyde solution into the homogeneous mixed solution and stir evenly to allow the mixed solution to undergo a cross-linking polymerization reaction to proceed fully, thereby obtaining a homogeneous bio-based chitosan hybrid sol.
[0037] The third step is to prepare the final bio-based chitosan hybrid gel:
[0038] 3.1 The bio-based chitosan hybrid sol prepared in the second step was placed in a glass crystallization dish, sealed and left to stand to wait for gelation, and the bio-based chitosan hybrid initial gel was obtained after 6 hours;
[0039] 3.2 Place the bio-based chitosan hybrid initial gel in a water bath for programmed temperature aging. The programmed temperature increase rate is 5°C / h, from room temperature (25°C) to 35°C, 45°C, 55°C, and 65°C in sequence. Each stage is replaced once with ethanol (purity 99.5%) and kept warm for 2h;
[0040] 3.3 Continue to raise the temperature to 75°C at the same heating rate as step 3.2 and keep warm for 2 hours. Place the bio-based chitosan hybrid gel in analytical pure ethanol solvent (purity is 99.5%) at room temperature to observe whether the bio-based chitosan hybrid initial gel can float directly. If it can float directly, it indicates that the gel aging and solvent replacement are completed, and the bio-based chitosan hybrid final gel is obtained.
[0041] The fourth step is to prepare lightweight and high-strength bio-based chitosan hybrid aerogel:
[0042] The chitosan hybrid final gel obtained in the third step was placed in a CO2 supercritical fluid drying device, heated to 60°C, filled with CO2 to 15MPa, and dried for 10 hours. After drying, the pressure was slowly released at a rate of 200kPa / min to finally obtain a lightweight and high-strength bio-based chitosan hybrid aerogel.
[0043] The density of the lightweight and high-strength bio-based chitosan hybrid aerogel thermal insulation material prepared in this example is 0.086 g / cm 3 The thermal conductivity at room temperature and pressure is 0.0262W / (m·K), and when the compressive strain is 3%, the compressive stress reaches 0.210MPa.
[0044] Embodiment 56
[0045] The first step is to prepare the bio-based chitosan solution:
[0046] 0.4 g of bio-based chitosan powder (deacetylation degree of 75%, viscosity of 205 mPa·s) was dissolved in 99.6 g of a mixed solvent of acetic acid (purity 99.5%), ethanol (purity 99.5%) and water (mass ratio of 1:80:44), and stirred evenly to obtain 100 g of a bio-based chitosan solution with a concentration of 0.4 wt.%.
[0047] The second step is to prepare the bio-based chitosan hybrid sol:
[0048] 2.1 Add 50 g of 5 wt.% polyvinyl alcohol solution (with a degree of alcoholysis of 86% and a viscosity of 105 mPa·s) to the 100 g bio-based chitosan solution prepared in the first step, and continue stirring until uniform. Then, slowly add 6 g of silicon oxide to the mixed solution and stir for 1 h. After uniform dispersion, add 18 g of 0.8 wt.% nanocellulose (with an aspect ratio of 35) and stir to obtain a homogeneous mixed solution.
[0049] 2.2 Add 26 g of 8 wt.% formaldehyde solution into the homogeneous mixed solution and stir evenly to allow the mixed solution to undergo a cross-linking polymerization reaction to proceed fully, thereby obtaining a homogeneous bio-based chitosan hybrid sol.
[0050] The third step is to prepare the final bio-based chitosan hybrid gel:
[0051] 3.1 The bio-based chitosan hybrid sol prepared in the second step was placed in a glass crystallization dish, sealed and left to stand to wait for gelation, and the bio-based chitosan hybrid initial gel was obtained after 6 hours;
[0052] 3.2 Place the bio-based chitosan hybrid initial gel in a water bath for programmed temperature aging. The programmed temperature increase rate is 5°C / h, from room temperature (25°C) to 35°C, 45°C, 55°C, and 65°C in sequence. Each stage is replaced once with ethanol (purity 99.5%) and kept warm for 2h;
[0053] 3.3 Continue to raise the temperature to 75°C at the same heating rate as step 3.2 and keep warm for 2 hours. Place the bio-based chitosan hybrid gel in analytical pure ethanol solvent (purity is 99.5%) at room temperature to observe whether the bio-based chitosan hybrid initial gel can float directly. If it can float directly, it indicates that the gel aging and solvent replacement are completed, and the bio-based chitosan hybrid final gel is obtained.
[0054] The fourth step is to prepare lightweight and high-strength bio-based chitosan hybrid aerogel:
[0055] The chitosan hybrid final gel obtained in the third step was placed in a CO2 supercritical fluid drying device, heated to 60°C, filled with CO2 to 15MPa, and dried for 10 hours. After drying, the pressure was slowly released at a rate of 200kPa / min to finally obtain a lightweight and high-strength bio-based chitosan hybrid aerogel.
[0056] The density of the lightweight and high-strength bio-based chitosan hybrid aerogel thermal insulation material prepared in this example is 0.158 g / cm 3 The thermal conductivity at room temperature and pressure is 0.0245 W / (m·K), and when the compressive strain is 3%, the compressive stress reaches 0.276 MPa.
[0057] Embodiment 109
[0058] The first step is to prepare the bio-based chitosan solution:
[0059] 1 g of bio-based chitosan powder (deacetylation degree of 75%, viscosity of 205 mPa·s) was dissolved in 99 g of a mixed solvent of acetic acid (purity 99.5%), ethanol (purity 99.5%) and water (mass ratio of 1:80:44), and stirred evenly to obtain 100 g of a bio-based chitosan solution with a concentration of 1 wt.%.
[0060] The second step is to prepare the bio-based chitosan hybrid sol:
[0061] 2.1 Add 50 g of 1 wt.% polyvinyl alcohol solution (with a degree of alcoholysis of 86% and a viscosity of 105 mPa·s) to the 100 g bio-based chitosan solution prepared in the first step, and continue stirring until uniform. Then, slowly add 6 g of zirconium oxide to the mixed solution and stir for 1 h. After uniform dispersion, add 18 g of 0.8 wt.% nanocellulose (with an aspect ratio of 35) and stir to obtain a homogeneous mixed solution.
[0062] 2.2 Add 26 g of 4 wt.% formaldehyde solution into the homogeneous mixed solution and stir evenly to allow the mixed solution to undergo a cross-linking polymerization reaction to proceed fully, thereby obtaining a homogeneous bio-based chitosan hybrid sol.
[0063] The third step is to prepare the final bio-based chitosan hybrid gel:
[0064] 3.1 The bio-based chitosan hybrid sol prepared in the second step was placed in a glass crystallization dish, sealed and left to stand to wait for gelation, and the bio-based chitosan hybrid initial gel was obtained after 6 hours;
[0065] 3.2 Place the bio-based chitosan hybrid initial gel in a water bath for programmed temperature aging. The programmed temperature increase rate is 5°C / h, from room temperature (25°C) to 35°C, 45°C, 55°C, and 65°C in sequence. Each stage is replaced once with ethanol (purity 99.5%) and kept warm for 2h;
[0066] 3.3 Continue to raise the temperature to 75°C at the same heating rate as step 3.2 and keep warm for 2 hours. Place the bio-based chitosan hybrid gel in analytical pure ethanol solvent (purity is 99.5%) at room temperature to observe whether the bio-based chitosan hybrid initial gel can float directly. If it can float directly, it indicates that the gel aging and solvent replacement are completed, and the bio-based chitosan hybrid final gel is obtained.
[0067] The fourth step is to prepare lightweight and high-strength bio-based chitosan hybrid aerogel:
[0068] The chitosan hybrid final gel obtained in the third step was placed in a CO2 supercritical fluid drying device, heated to 60°C, filled with CO2 to 15MPa, and dried for 10 hours. After drying, the pressure was slowly released at a rate of 200kPa / min to finally obtain a lightweight and high-strength bio-based chitosan hybrid aerogel.
[0069] The density of the lightweight and high-strength bio-based chitosan hybrid aerogel thermal insulation material prepared in this example is 0.158 g / cm 3 The thermal conductivity at room temperature and pressure is 0.0253W / (m·K), and when the compressive strain is 3%, the compressive stress reaches 0.269MPa.
[0070] Embodiment 181
[0071] The first step is to prepare the bio-based chitosan solution:
[0072] 1 g of bio-based chitosan powder (deacetylation degree of 75%, viscosity of 205 mPa·s) was dissolved in 99 g of a mixed solvent of acetic acid (purity 99.5%), ethanol (purity 99.5%) and water (mass ratio of 1:80:44), and stirred evenly to obtain 100 g of a bio-based chitosan solution with a concentration of 1 wt.%.
[0073] The second step is to prepare the bio-based chitosan hybrid sol:
[0074] 2.1 Add 50 g of 8 wt.% polyvinyl alcohol solution (with a degree of alcoholysis of 86% and a viscosity of 105 mPa·s) to the 100 g bio-based chitosan solution prepared in the first step, and continue stirring until uniform. Then, slowly add 6 g of zirconium oxide to the mixed solution and stir for 1 h. After uniform dispersion, add 18 g of 0.8 wt.% nanocellulose (with an aspect ratio of 35) and stir to obtain a homogeneous mixed solution.
[0075] 2.2 Add 26 g of 4 wt.% formaldehyde solution into the homogeneous mixed solution and stir evenly to allow the mixed solution to undergo a cross-linking polymerization reaction to proceed fully, thereby obtaining a homogeneous bio-based chitosan hybrid sol.
[0076] The third step is to prepare the final bio-based chitosan hybrid gel:
[0077] 3.1 The bio-based chitosan hybrid sol prepared in the second step was placed in a glass crystallization dish, sealed and left to stand to wait for gelation, and the bio-based chitosan hybrid initial gel was obtained after 6 hours;
[0078] 3.2 Place the bio-based chitosan hybrid initial gel in a water bath for programmed temperature aging. The programmed temperature increase rate is 5°C / h, from room temperature (25°C) to 35°C, 45°C, 55°C, and 65°C in sequence. Each stage is replaced once with ethanol (purity 99.5%) and kept warm for 2h;
[0079] 3.3 Continue to raise the temperature to 75°C at the same heating rate as step 3.2 and keep warm for 2 hours. Place the bio-based chitosan hybrid gel in analytical pure ethanol solvent (purity is 99.5%) at room temperature to observe whether the bio-based chitosan hybrid initial gel can float directly. If it can float directly, it indicates that the gel aging and solvent replacement are completed, and the bio-based chitosan hybrid final gel is obtained.
[0080] The fourth step is to prepare lightweight and high-strength bio-based chitosan hybrid aerogel:
[0081] The chitosan hybrid final gel obtained in the third step was placed in a CO2 supercritical fluid drying device, heated to 60°C, filled with CO2 to 15MPa, and dried for 10 hours. After drying, the pressure was slowly released at a rate of 200kPa / min to finally obtain a lightweight and high-strength bio-based chitosan hybrid aerogel.
[0082] The density of the lightweight and high-strength bio-based chitosan hybrid aerogel thermal insulation material prepared in this example is 0.197 g / cm 3 The thermal conductivity at room temperature and pressure is 0.0226W / (m·K), and when the compressive strain is 3%, the compressive stress reaches 0.264MPa.
[0083] Embodiment 232
[0084] The first step is to prepare the bio-based chitosan solution:
[0085] 2.3 g of bio-based chitosan powder (deacetylation degree of 75%, viscosity of 205 mPa·s) was dissolved in 97.7 g of a mixed solvent of acetic acid (purity 99.5%), ethanol (purity 99.5%) and water (mass ratio of 1:80:44), and stirred evenly to obtain 100 g of a bio-based chitosan solution with a concentration of 2.3 wt.%.
[0086] The second step is to prepare the bio-based chitosan hybrid sol:
[0087] 2.1 Add 50 g of 1 wt.% polyvinyl alcohol solution (with a degree of alcoholysis of 86% and a viscosity of 105 mPa·s) to the 100 g bio-based chitosan solution prepared in the first step, and continue stirring until uniform. Then, slowly add 6 g of zirconium oxide to the mixed solution and stir for 1 h. After uniform dispersion, add 18 g of 5.5 wt.% nanocellulose (with an aspect ratio of 35) and stir to obtain a homogeneous mixed solution.
[0088] 2.2 Add 26 g of 4 wt.% glutaraldehyde solution into the homogeneous mixed solution and stir evenly to allow the mixed solution to undergo a cross-linking polymerization reaction to proceed fully, thereby obtaining a homogeneous bio-based chitosan hybrid sol.
[0089] The third step is to prepare the final bio-based chitosan hybrid gel:
[0090] 3.1 The bio-based chitosan hybrid sol prepared in the second step was placed in a glass crystallization dish, sealed and left to stand to wait for gelation, and the bio-based chitosan hybrid initial gel was obtained after 6 hours;
[0091] 3.2 Place the bio-based chitosan hybrid initial gel in a water bath for programmed temperature aging. The programmed temperature increase rate is 5°C / h, from room temperature (25°C) to 35°C, 45°C, 55°C, and 65°C in sequence. Each stage is replaced once with ethanol (purity 99.5%) and kept warm for 2h;
[0092] 3.3 Continue to raise the temperature to 75°C at the same heating rate as step 3.2 and keep warm for 2 hours. Place the bio-based chitosan hybrid gel in analytical pure ethanol solvent (purity is 99.5%) at room temperature to observe whether the bio-based chitosan hybrid initial gel can float directly. If it can float directly, it indicates that the gel aging and solvent replacement are completed, and the bio-based chitosan hybrid final gel is obtained.
[0093] The fourth step is to prepare lightweight and high-strength bio-based chitosan hybrid aerogel:
[0094] The chitosan hybrid final gel obtained in the third step was placed in a CO2 supercritical fluid drying device, heated to 60°C, filled with CO2 to 15MPa, and dried for 10 hours. After drying, the pressure was slowly released at a rate of 200kPa / min to finally obtain a lightweight and high-strength bio-based chitosan hybrid aerogel.
[0095] The density of the lightweight and high-strength bio-based chitosan hybrid aerogel thermal insulation material prepared in this example is 0.076 g / cm 3 The thermal conductivity at room temperature and pressure is 0.0189 W / (m·K), and when the compressive strain is 3%, the compressive stress reaches 0.212 MPa.
[0096] Embodiment 277
[0097] The first step is to prepare the bio-based chitosan solution:
[0098] 2.3 g of bio-based chitosan powder (deacetylation degree of 75%, viscosity of 205 mPa·s) was dissolved in 97.7 g of a mixed solvent of acetic acid (purity 99.5%), ethanol (purity 99.5%) and water (mass ratio of 1:80:44), and stirred evenly to obtain 100 g of a bio-based chitosan solution with a concentration of 2.3 wt.%.
[0099] The second step is to prepare the bio-based chitosan hybrid sol:
[0100] 2.1 Add 50 g of 5 wt.% polyvinyl alcohol solution (with a degree of alcoholysis of 86% and a viscosity of 105 mPa·s) to the 100 g bio-based chitosan solution prepared in the first step, and continue stirring until uniform. Then, slowly add 6 g of silicon oxide to the mixed solution and stir for 1 h. After uniform dispersion, add 18 g of 3 wt.% nanocellulose (with an aspect ratio of 35) and stir to obtain a homogeneous mixed solution.
[0101] 2.2 Add 26 g of 4 wt.% formaldehyde solution into the homogeneous mixed solution and stir evenly to allow the mixed solution to undergo a cross-linking polymerization reaction to proceed fully, thereby obtaining a homogeneous bio-based chitosan hybrid sol.
[0102] The third step is to prepare the final bio-based chitosan hybrid gel:
[0103] 3.1 The bio-based chitosan hybrid sol prepared in the second step was placed in a glass crystallization dish, sealed and left to stand to wait for gelation, and the bio-based chitosan hybrid initial gel was obtained after 6 hours;
[0104] 3.2 Place the bio-based chitosan hybrid initial gel in a water bath for programmed temperature aging. The programmed temperature increase rate is 5°C / h, from room temperature (25°C) to 35°C, 45°C, 55°C, and 65°C in sequence. Each stage is replaced once with ethanol (purity 99.5%) and kept warm for 2h;
[0105] 3.3 Continue to raise the temperature to 75°C at the same heating rate as step 3.2 and keep warm for 2 hours. Place the bio-based chitosan hybrid gel in analytical pure ethanol solvent (purity is 99.5%) at room temperature to observe whether the bio-based chitosan hybrid initial gel can float directly. If it can float directly, it indicates that the gel aging and solvent replacement are completed, and the bio-based chitosan hybrid final gel is obtained.
[0106] The fourth step is to prepare lightweight and high-strength bio-based chitosan hybrid aerogel:
[0107] The chitosan hybrid final gel obtained in the third step was placed in a CO2 supercritical fluid drying device, heated to 60°C, filled with CO2 to 15MPa, and dried for 10 hours. After drying, the pressure was slowly released at a rate of 200kPa / min to finally obtain a lightweight and high-strength bio-based chitosan hybrid aerogel.
[0108] The density of the lightweight and high-strength bio-based chitosan hybrid aerogel thermal insulation material prepared in this example is 0.125 g / cm 3 The thermal conductivity at room temperature and pressure is 0.0254W / (m·K), and when the compressive strain is 3%, the compressive stress reaches 0.225MPa.
[0109] Examples 2-55, 57-108, 110-180, 182-231, 233-276, 278-324
[0110] The process parameters used in Examples 2 to 55, 57 to 108, 110 to 180, 182 to 231, 233 to 276, and 278 to 324 are shown in Table 1, wherein the concentration of the bio-based chitosan solution, the concentration of the polyvinyl alcohol solution, the type and amount of the metal oxide or non-metal oxide, the type of nanocellulose, and the type of the crosslinking agent and the concentration of the crosslinking agent solution are the main factors affecting the experimental data such as the density of the aerogel material, the thermal conductivity at room temperature and pressure, and the mechanical strength performance. The experimental process parameters not indicated in the table have basically no effect on the above experimental data results of the aerogel material. As long as they are within the range described in the content of the invention, the aerogel of the present invention can be prepared. For simplicity and convenience, the other parameters of Examples 2 to 55, 57 to 108, 110 to 180, 182 to 231, 233 to 276, and 278 to 324 are the same as those of Example 1. The specific parameters are as follows:
[0111] In the first step, the bio-based chitosan powder is selected to have a deacetylation degree of 75%, a viscosity of 205 mPa·s, an acetic acid purity of 99.5%, an ethanol purity of 99.5%, and a mixed solvent volume ratio of acetic acid, ethanol and water of 1:80:44. The selection of each parameter in this step only enables the chitosan powder to be uniformly dissolved and the reaction to proceed normally, and does not affect the density, thermal conductivity at room temperature and pressure, and mechanical strength properties of the material of the present invention, and there is no special requirement.
[0112] In the second step, the polyvinyl alcohol solution is selected to have a degree of alcoholysis of 86% and a viscosity of 105 mPa·s. Both of them only affect the dissolution of polyvinyl alcohol, and do not affect the density, thermal conductivity at room temperature and pressure, and mechanical strength properties of the aerogel material; the aspect ratio of the nanocellulose selected in the embodiment is 35, and the amount of metal oxide (zirconium oxide) or non-metal oxide (silicon oxide) added is based on the mass of the bio-based chitosan solution, and 6% of the mass of the bio-based chitosan solution is selected for zirconium oxide or silicon oxide. The addition of polyvinyl alcohol solution and metal oxide or non-metal oxide has a great influence on the preparation and test performance (density, thermal conductivity at room temperature and pressure, and mechanical strength properties) of the bio-based chitosan hybrid aerogel, and the obtained mixed solution must be stirred evenly.
[0113] In the third step, the time for the bio-based chitosan solution to stand and wait for gelation, the starting temperature and heating rate of the water bath, and the insulation time of each temperature step are determined according to the actual experimental results and are only used as reference in the embodiments; the organic solvent selected in the solvent replacement stage (one or two or a mixture of multiple solvents such as methanol, ethanol and isopropanol) is exchanged with the water molecules inside the three-dimensional network of the bio-based chitosan gel and some residual substances that have not completely participated in the reaction. The network skeleton of the bio-based chitosan gel is not destroyed during the replacement period, and the above parameters do not affect the density, thermal conductivity at room temperature and pressure, and mechanical strength properties of the aerogel material.
[0114] The temperature and pressure adopted in the supercritical fluid drying method used in the fourth step are basic parameters set to maintain the supercritical fluid state of carbon dioxide. They can maintain the rich network skeleton structure of the bio-based chitosan hybrid aerogel without affecting the density of the aerogel material, thermal conductivity at room temperature and pressure, and mechanical strength properties.
[0115] Table 1 Preparation process parameters of lightweight and high-strength bio-based chitosan hybrid aerogel
[0116]
[0117]
[0118]
[0119]
[0120]
[0121]
[0122]
[0123]
[0124]
[0125]
[0126]
[0127]
[0128] Summarizing the above table, we found that:
[0129] (1) Bio-based chitosan solution affects the density and mechanical properties of aerogels. Generally, the higher the concentration, the greater the density of the prepared aerogel, but its compressive stress may also increase, because a high concentration solution leads to a tighter network structure. The preferred concentration of the bio-based chitosan solution is 0.6-1.7 wt.%.
[0130] (2) The addition of polyvinyl alcohol helps to improve the mechanical properties of aerogels. A higher polyvinyl alcohol concentration will increase the compressive stress of the aerogel, but may also slightly increase the density because polyvinyl alcohol, as a reinforcing agent, helps to form a stronger cross-linked network. The preferred polyvinyl alcohol solution concentration is 2 to 6 wt.%.
[0131] (3) The addition of nanocellulose helps to improve the mechanical properties of aerogels, and the increase in dosage usually increases the compressive stress, but has little effect on the density. Nanocellulose enhances the three-dimensional network structure of aerogels by forming hydrogen bonds or reacting with other groups. The concentration of the nanocellulose solution after optimization is 0.8-4wt.%.
[0132] (4) The type and concentration of the cross-linking agent have a significant effect on the mechanical properties of the aerogel. Using different cross-linking agents or adjusting their concentrations can change the compressive stress and density of the aerogel. High concentrations of cross-linking agents may increase the compressive stress of the aerogel because they promote stronger intermolecular cross-linking. The preferred cross-linking agent is formaldehyde, with a solution concentration of 7 to 12 wt.%.
[0133] In summary, by adjusting the above process parameters, the density, compressive stress and thermal conductivity of bio-based chitosan hybrid aerogels can be regulated to a certain extent to meet specific application requirements.
Claims
1. A lightweight and high-strength bio-based chitosan hybrid aerogel, characterized in that Lightweight and high-strength bio-based chitosan hybrid aerogel is made of chitosan, polyvinyl alcohol, nanocellulose and metal oxides or non-metal oxides as raw materials, mixed in a mass ratio of 1:0.3-0.8:0.03-0.2:0.01-0.1, and the amounts of other added phases are based on the chitosan solution of the ternary solvent of acetic acid, ethanol and water, and stirred evenly to obtain a mixed solution; a cross-linking agent is added to the mixed solution, and the mass ratio of the cross-linking agent to the mixed solution is 0.15-0.35:1, and the bio-based chitosan gel is prepared by a sol-gel method; it is prepared through a programmed staged heating aging, solvent replacement, and finally CO2 supercritical fluid drying; the bio-based chitosan hybrid aerogel has a nanoporous three-dimensional network skeleton.
2. A lightweight and high-strength bio-based chitosan hybrid aerogel as claimed in claim 1, characterized in that The chitosan solution has a concentration of 0.4-2.3 wt.%, the polyvinyl alcohol solution has a concentration of 1-8 wt.%, the nanocellulose solid content has a concentration of 0.5-5.5 wt.%, and the crosslinker solution has a concentration of 4-12 wt.%.
3. A method for preparing the lightweight and high-strength bio-based chitosan hybrid aerogel as claimed in claim 1, characterized in that it comprises the following steps: The first step is to prepare a bio-based chitosan solution by: The bio-based chitosan powder is dissolved in a mixed solvent of acetic acid, ethanol and water, and the mixture is stirred and dissolved to obtain a bio-based chitosan solution; The bio-based chitosan powder has a deacetylation degree of 35% to 95%, a viscosity of 99 to 510 mPa·s, and a bio-based chitosan solution concentration, i.e., a bio-based chitosan powder concentration in a mixed solvent of 0.4 to 2.3 wt.%; The mass ratio of acetic acid, ethanol and water in the mixed solvent is 1:60-90:40-60; The second step is to prepare the bio-based chitosan hybrid sol as follows: 2.1 Add polyvinyl alcohol solution to the bio-based chitosan solution prepared in the first step, stir evenly, then add metal oxide or non-metal oxide, after the metal oxide or non-metal oxide is evenly dispersed, add nanocellulose and continue stirring to form van der Waals force, hydrogen bond and physical entanglement between chitosan molecular chains, polyvinyl alcohol molecular chains and nanocellulose molecules, and obtain a homogeneous mixed solution; the polyvinyl alcohol solution has a degree of alcoholysis of 68% to 99%, a viscosity of 18 to 113 mPa·s, and a concentration of 1 to 8 wt.%; The metal oxide or non-metal oxide is based on the chitosan solution and is added in an amount of 1% to 10% of the mass of the chitosan solution; The nanocellulose has a solid content of 0.5 to 5.5 wt.%, and an aspect ratio of 15 to 55; 2.2 Add the crosslinking agent solution to the homogeneous mixed solution, stir evenly to make the mixed solution with the crosslinking agent solution undergo crosslinking polymerization, and the aldehyde group in the crosslinking agent and the amino group in the chitosan molecule undergo acetal reaction to obtain a homogeneous bio-based chitosan hybrid sol; the mass ratio of the homogeneous mixed solution to the crosslinking agent solution is 1:0.15-0.35; The crosslinking agent in the crosslinking agent solution is any one of formaldehyde, acetaldehyde, propionaldehyde, glutaraldehyde, o-phthalaldehyde, isophthalaldehyde, terephthalaldehyde, or a mixed solvent of two or more thereof, with a concentration of 4 to 12 wt.%; The third step is to prepare the bio-based chitosan hybrid final gel as follows: 3.1 The homogeneous bio-based chitosan hybrid sol prepared in the second step is aged at room temperature to form a bio-based chitosan hybrid initial gel; 3.2 The bio-based chitosan hybrid initial gel is placed in a water bath and subjected to programmed temperature rise for further aging, while the organic alcohol solvent is used to replace the solvent; the programmed temperature rise step is from room temperature to 35°C, 45°C, 55°C, and 65°C in sequence, with a heating rate of 4-6°C / h, and the organic solvent is replaced once in each stage and kept warm for 2-6h; the room temperature is 25°C; 3.3 Continue to heat the temperature to 75°C at the same heating rate as step 3.2, and keep the temperature for 2 to 6 hours. Place the bio-based chitosan hybrid gel in an analytical pure ethanol solvent at room temperature to observe whether the bio-based chitosan hybrid initial gel can float directly. If it floats directly, it indicates that the gel aging and solvent replacement are completed, and the bio-based chitosan hybrid final gel is obtained; The organic solvent used in the solvent replacement is any one of methanol, ethanol, isopropanol, and n-propanol, or a mixed solvent of two or more thereof; The fourth step is to prepare a lightweight and high-strength bio-based chitosan hybrid aerogel by: The final bio-based chitosan hybrid gel obtained in the third step is placed in a drying kettle for CO2 supercritical fluid drying, and after drying, the pressure is released to obtain a lightweight and high-strength bio-based chitosan hybrid aerogel; The CO2 supercritical fluid drying has a pressure of 8 to 19 MPa, a drying time of 6 to 20 hours, a temperature of 37 to 82°C, and a pressure release rate of 90 to 243 kPa / min.
4. A method for preparing a lightweight and high-strength bio-based chitosan hybrid aerogel as claimed in claim 3, characterized in that In the first step, the bio-based chitosan powder has a deacetylation degree of 68% to 95%, a viscosity of 99 to 205 mPa·s, and a bio-based chitosan solution concentration of 0.6 to 1.7 wt. %; the acetic acid purity in the mixed solvent is 99.5% to 99.9%, and the ethanol purity is 99.3% to 99.9%.
5. A method for preparing a lightweight and high-strength bio-based chitosan hybrid aerogel as claimed in claim 3, characterized in that The polyvinyl alcohol solution in step 2.1 has a degree of alcoholysis of 86-90 mol%, a viscosity of 78-113 mPa·s, and a concentration of 2-6 wt.%; the metal oxide or non-metal oxide is any one of iron oxide, aluminum oxide, zirconium oxide, silicon oxide, and calcium oxide, or a mixed oxide of two or more thereof; the nanocellulose is any one of waste paper nanocellulose, graphene nanocellulose, bacterial nanocellulose, fungal nanocellulose, and wood nanocellulose, or a mixed cellulose of two or more thereof, with a solid content of 0.8-4 wt.% and an aspect ratio of 26-42.
6. A method for preparing a lightweight and high-strength bio-based chitosan hybrid aerogel as claimed in claim 5, characterized in that The metal oxide is zirconium oxide, namely ZrO2, and the non-metal oxide is silicon oxide, namely SiO2.
7. A method for preparing a lightweight and high-strength bio-based chitosan hybrid aerogel as claimed in claim 3, characterized in that In step 2.2, the crosslinking agent in the crosslinking agent solution is formaldehyde with a concentration of 7 to 12 wt.%.
8. A method for preparing a lightweight and high-strength bio-based chitosan hybrid aerogel as claimed in claim 3, characterized in that The organic solvent used in the solvent replacement in step 3.3 is ethanol.
9. A method for preparing a lightweight and high-strength bio-based chitosan hybrid aerogel as claimed in claim 3, characterized in that The purity of the methanol, ethanol, isopropanol and n-propanol in step 3.3 is required to be above 99%, and the purity of the analytical grade ethanol solvent is 99.3% to 99.9%.
10. A method for preparing a lightweight and high-strength bio-based chitosan hybrid aerogel as claimed in claim 3, characterized in that In the fourth step, the pressure of the CO2 supercritical fluid drying is 13-18 MPa, the drying time is 7-16 hours, the temperature is 48-63°C, and the pressure release rate is 118-178 kPa / min.
Citation Information
Patent Citations
Chitin-chitosan-based bi-crosslinking aerogel and preparation method thereof
CN115536896A
Natural nano cellulose-based composite heat-insulating aerogel and preparation method thereof
CN110157044A
Method used for modifying CS-SiO2 aerogel with cellulose
CN110240730A
Super-hydrophobic chitosan hybrid aerogel and preparation method thereof
CN115124760A
Freeze-drying preparation method of chitosan-silicon dioxide hybrid aerogel
CN115449119A
Cited By
Cooking-resistant PE suction nozzle cover and preparation method thereof
CN119912743A